Early Miocene remains of Melissiodon from Mokrá-Quarry (Moravia, Czech Republic) shed light on the evolutionary history of the rare cricetid genus - Bonilla-Salomón, Isaac; Čermák, Stanislav; Luján, Àngel H.; Jovells-Vaqué, Sílvia; Ivanov, Martin; Sabol, Martin (PeerJ, 2022)
Background Melissiodon is a rare cricetid genus endemic to Europe, known from the Early Oligoceneto the Early Miocene. It is usually a very rare find, and even in the few localities where Melissiodon remains are found, those are scarce and fragmentary. Only a few Central European localities have yielded rich remains of the genus. Currently, two species are known from the Early Miocene: Melissiodon schlosseri, which is based on two teeth from the MN2 German locality of Haslach and only found in two other sites of similar age (Ulm-Uniklinik and La Chaux, from Germany and Switzerland respectively); and Melissiodon dominans, found in MN3 and MN4 localities across Europe, even though the scarce and fragmentary remains make some of these attributions dubious. For that reason, Melissiodon dominans has become a catch-all species. However, Mokrá-Quarry represents one of the best documented findings of Melissiodon remains from MN4 localities of Europe. Methods The Melissiodon assemblage from Mokrá-Quarry has been studied thoroughly, providing metrics and detailed descriptions of all teeth positions, as well as complete comparisons with other MN3 and MN4 localities bearing Melissiodon remains. Results In this work, new remains of Melissiodon have been identified as a new morphotype that clearly differs from Melissiodon dominans by its unique m1 morphology but still shows some resemblance with Melissiodon schlosseri. Based on that, we here propose the hypothesis of an evolutionary lineage starting from Melissiodon schlosseri, diverging from the lineage leading towards Melissiodon dominans. With this finding, there are at least two different taxa of Melissiodon known during the Early Miocene, prior to the genus extinction. This study arises the certainty that the evolution history of the genus is more complex than previously thought and that more studies are necessary to elucidate it, including a complete revision of the type material of Melissiodon dominans and Melissiodon schlosseri in the light of current knowledge of the genus, which will help to elucidate the attribution of the populations from Mokrá-Quarry. For the time being, the assemblage presented here is referred as Melissiodon aff. schlosseri.
Keywords: Melissiodontinae; Melissiodon schlosseri; Melissiodon dominans; Burdigalian; Carpathian Foredeep Basin; Moravian Karst